Malaria prevalence, knowledge and associated factors among household heads in Maygaba town, Ethiopia - Tsegay Gebremaryam Yhdego; Asnake Desalegn Gardew; Fitsum Tigu Yifat (Public Library of Science (PLoS), 2022)
Malaria remains a leading public health issue in Ethiopia, despite wide use of insecticide-treated mosquito nets (ITNs). Consistent use of ITNs reduces malaria transmission by 90%. However, coverage and proper use of ITNs are the major challenge for most rural settings of Ethiopia. We assessed the prevalence of malaria, ITNs use and associated factors among household heads in Maygaba town, northwest Ethiopia. A cross-sectional study was carried out among 403 households using a structured questionnaire. Blood samples were collected from household heads and examined for malaria parasites by microscopy. Chi-square test and logistic regression were used to check the association between the dependent and independent variables. Of the 403 blood samples, 19 (4.7%) had malaria parasites (12 cases of Plasmodium falciparum and 7 cases of Plasmodium vivax). Majority of the respondents were aware of the cause, communicability, preventability and curability of the disease. ITNs use was identified as the main malaria prevention method. About 64% (257) of the respondents owned ITNs, of which, 66.9% (172) consistently slept under the nets during the peak malaria season. Majority of the respondents (83.6%) had positive attitude towards the benefit of sleeping under ITNs. Educational status and livelihood of the respondents had statistically significant (p < 0.05) association with malaria knowledge. Malaria infection was significantly (p < 0.05) higher among household heads aged 18-30 years (AOR = 5.982; 95% CI = 1.715-20.863). Moderate prevalence rate and acceptable ITNs ownership was detected among the community of Maygaba town. However, a considerable proportion had misconceptions about the use of ITNs. A comprehensive malaria control measures and health education about the use of ITNs should be in place for effective prevention and control of malaria in the locality.